Media Edukasi Berbasis Cetak dan Digital Tentang Pengobatan Lepra dan Efek Samping Obat Mempermudah Pemahaman Penderita Lepra, Keluarga, Masyarakat dan Tenaga Kesehatan di Tanjung Pasir Tentang Lepra dan Terapinya - Rika Yuliwulandari; Hilyatuz Zahroh; Retno Wilujeng Susilowati; Faradyna Hendri; Herman Usman (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2017)
Leprosy can be cured with multi-drug therapy as recommended by WHO. However, the presence of leprosy stigma prevents people from obtaining early detection and proper treatment. Furthermore, the adverse effect of leprosy treatment on certain individuals with genetic susceptibility, known as dapsone hypersensitivity syndrome, is often presumed as a malpractice. This further lowered people willingness to seek medical help. The reluctance to cure the disease could worsen the disease condition and spread it to their community. To overcome these problems, there should be efforts to disseminate medical information to community which discuss about leprosy treatment and its possible adverse effect. In this activity we, together with Puskesmas Desa Tegal Angus, informed and educated leprosy patients, their family and their neighbouring community with the help of educational media in the form of print and digital media. The aim of this activity was to share correct information on leprosy and the urgency of leprosy treatment, which in turn would reduce leprosy stigma and increase the patients’ willingness to complete their full course of treatment. According to the test result, people gained improved understanding about leprosy, especially in term of its definition, its transmission and treatment, factors that influence its susceptibility (including genetic factor) and how to avoid deformity due to leprosy.